Dubravka Oraić Tolić’s Thoughts on Antun Gustav Matoš - Dujić, Tatjana (Poznańskie Studia Slawistyczne, 2014)
The purpose of this appendage (addendum) is to study a position of the female subject in the fictional prosem of Antun Gustav Matoš through the reading of Dubravka Oraić Tolić. This research has shown that female subjects carry, or better to say, possess all features of Matoš’s poetic expression, therefore it is possible to sort them into three different models: woman-mother, woman-aesthetic creation and femme fatale.